2022
DOI: 10.3390/biom12070866
|View full text |Cite
|
Sign up to set email alerts
|

Life and Death Decisions—The Many Faces of Autophagy in Cell Survival and Cell Death

Abstract: Autophagy is a process conserved from yeast to humans. Since the discovery of autophagy, its physiological role in cell survival and cell death has been intensively investigated. The inherent ability of the autophagy machinery to sequester, deliver, and degrade cytoplasmic components enables autophagy to participate in cell survival and cell death in multiple ways. The primary role of autophagy is to send cytoplasmic components to the vacuole or lysosomes for degradation. By fine-tuning autophagy, the cell reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Autophagic death is a controversial idea that has been discussed and debated many times. Autophagy is considered as a two-faced process: it can ensure cell survival as well as promote cell death [ 86 ]. However, it is difficult to distinguish when the occurrence of autophagic-related structures and recruitment of Atg genes function with the aim of cell survival and, conversely, when the aim is cell death.…”
Section: Autophagy Contribution To Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagic death is a controversial idea that has been discussed and debated many times. Autophagy is considered as a two-faced process: it can ensure cell survival as well as promote cell death [ 86 ]. However, it is difficult to distinguish when the occurrence of autophagic-related structures and recruitment of Atg genes function with the aim of cell survival and, conversely, when the aim is cell death.…”
Section: Autophagy Contribution To Cell Deathmentioning
confidence: 99%
“…Therefore, crosstalk between these two processes remains important to study. Many genes are involved in both autophagy and cell death in animal models [ 86 ]. Although our knowledge of this subject in plants is limited, a few examples of cell death with autophagy have been described, and VPEs, as proteases associated with cell death execution in plants, may be an important factor connected with the pro-death or pro-survival role of plant autophagy [ 25 , 32 ].…”
Section: Autophagy Contribution To Cell Deathmentioning
confidence: 99%
“…Selective autophagy processes contain proteins and specialized autophagic receptors which identify the cargo, generally mediated via cargo ubiquitination [ 30 ]. Through its interaction with a scaffold protein, the receptor either binds to cargoes or may be an integral component of these cargoes, connecting them to the autophagy machinery in the cell [ 31 ]. Protein aggregates are associated with Alzheimer’s, Parkinson’s, and Huntington’s diseases [ 2 , 32 ].…”
Section: Mechanism Of Autophagy Pathwaysmentioning
confidence: 99%
“… 112 , 114 Autophagic cell death describes an “excessive” degradation of important cellular components that are necessary for the normal cell function. 115 117 This deadly molecular mechanism brings to light the darker, concealed, Yin feature of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“… 122 125 Recent studies outlined the hypothesis that ROS are pawns with decisive roles in the fate of the molecular match of autophagic cell death. 114 116 It has been shown that the released lysosomal cathepsins have been involved in the oxidative stress–induced apoptosis. 122 125 Moreover, since lysosomes represent important sources of ROS, they might play important performances in the redox imbalance initiation and the exacerbation of oxidative stress, triggering oxidative cellular damages.…”
Section: Introductionmentioning
confidence: 99%